INSURANCE MARKETING STRATEGIES AND RISK PROTECTION AWARENESS AMONG SME OWNERS IN NORTHERN MALAYSIA - Dayang Hasliza Muhd Yusuf; Mohd Rosli Abdul Ghani; Muhammad Shahar Jusoh; Muhammad Nur Azizi Che Othman, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The study examines the effect of 7Ps of service marketing strategies and attitude towards risks on insurance purchase behaviour of SMEs as their risk mitigation and management. Despite the failure risks among SMEs, insurance penetration rates among SMEs are low, showing low risk protection awareness. Insurers need to understand the effectiveness of service marketing strategies in influencing SME owners’ purchase behaviour. The study uses paper-based surveys among 123 SMEs in Northern Malaysia. A set of survey questionnaire was developed based on adoption and adaptation items from existing studies. Data was analysed using PLS-SEM via SmartPLS 3.0. Findings indicated that only five of the service marketing strategies, namely price, promotion, place, process, and physical evidence have significant influence on the insurance purchase behaviour. In addition, attitude towards risks fully mediates all the direct effect of the five Ps, meaning that the SMEs attitude towards risks weakens the effect of all the marketing strategies on the SMEs insurance purchase behaviour. This study makes both theoretical and practical contributions, especially in identifying the roles of external stimuli and internal process in influencing insurance purchase behaviour among SMEs. The findings of the study will provide help to agencies tasked with developing SMEs in enhancing their risks management plan to protect the SMEs in facing the highly uncertain nature of the business; as well as insurers in increasing the penetration rates of insurance among SMEs.